2014
DOI: 10.1007/s11010-014-2262-5
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin reduces the amplitude of shortening and Ca2+ transient in ventricular myocytes from streptozotocin-induced diabetic rats

Abstract: In the management of type 2 diabetes mellitus, Dapagliflozin (DAPA) is a newly introduced selective sodium-glucose co-transporter 2 inhibitor which promotes renal glucose excretion. Little is known about the effects of DAPA on the electromechanical function of the heart. This study investigated the effects of DAPA on ventricular myocyte shortening and intracellular Ca(2+) transport in streptozotocin (STZ)-induced diabetic rats. Shortening, Ca(2+) transients, myofilament sensitivity to Ca(2+) and sarcoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…Previous studies showed that blood pressure control and weight loss were effective for improving ventricular repolarization abnormality [10,11]. The possibility of a direct effect of SGLT2 inhibitors on electrophysiology of the heart cannot be excluded, however, because SGLT2 inhibitors affect intracellular Ca 2+ handling and activity of the Na + /H + exchanger in cardiomyocytes [15,16]. In addition, change in QTc dispersion was positively correlated with change in systolic blood pressure, although the correlation was not very close.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies showed that blood pressure control and weight loss were effective for improving ventricular repolarization abnormality [10,11]. The possibility of a direct effect of SGLT2 inhibitors on electrophysiology of the heart cannot be excluded, however, because SGLT2 inhibitors affect intracellular Ca 2+ handling and activity of the Na + /H + exchanger in cardiomyocytes [15,16]. In addition, change in QTc dispersion was positively correlated with change in systolic blood pressure, although the correlation was not very close.…”
Section: Discussionmentioning
confidence: 96%
“…; Hamouda et al. ). Diabetes was induced in male (250 g) Wistar rats by a single intraperitoneal injection of STZ (60 mg/kg bodyweight) as previously described (Howarth et al.…”
Section: Methodsmentioning
confidence: 97%
“…; Hamouda et al. ). Bodyweight, nonfasting blood glucose, and heart weight were measured prior to the experiments.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study published in February 2015 showed that dapagliflozin alters the mechanism of calcium transport (L Ca + 2 current) which may partly exert the negative inotropic effects in ventricular myocytes from streptozotocin-treated and control rats [29].…”
Section: Animal Studies Showing Sglt2 Inhibitors and CV Outcomesmentioning
confidence: 99%